(untitled) (Global Journal of Sciences, 2025)
The idea of convexity is mainly employed in the realm of fractional calculus to address a number of issues in pure and practical research. The purpose of this review note is to demonstrate Hermite-Hadamard (H-H) inequalities via Caputo Fabrizio fractional integral operators associated with various topic of convexity.